FAKTOR-FAKTOR PENGARUH TINGKAT KECEMASAN PADA PASIEN FRAKTUR DENGAN POST OP ORIF: FAKTOR-FAKTOR PENGARUH TINGKAT KECEMASAN PADA PASIEN FRAKTUR DENGAN POST OP ORIF - Nofiah, Niafatun; Afifah, Vina Asna; Yunita (LPPM STIKes Bahrul Ulum Jombang, 2021)
ORIF (Open reduction internal fixation) is a management action given in cases of fractures that use surgical techniques, and can cause discomfort and cause anxiety in patients. This study is an analytical survey research with a cross sectional approach, when sampling using accidental sampling technique, and the sample in this study was fracture patients with Post ORIF surgery at Ngudi Waluyo Wlingi Hospital and obtained 32 respondents. The instrument used is the HARS questionnaire to assess the level of anxiety. Analysis of the data used is SPSS 16.0 software with linear regression test. The results of this study obtained factors that influence the level of anxiety in fractures with Post Orif Surgery at Ngudi Waluyo Wlingi Hospital, namely (p value = 0.039) and education (p value = 0.037). and factors that have no effect on gender, surgery history, type of surgery and medications you are taking. Conclusion: the most influential factor on the anxiety level of fracture patients with POST OP ORIF is education and then the patient's age.